Genocidal crimes - Alvarez, Alex (Key ideas in criminology, 2010)
Defining a crime -- States and genocide I : state crime and war -- States and genocide II : legitimacy and ideology -- Perpetrators I : the organizational context -- Perpetrators II : the individual context -- An end to genocide?